Performance of the EORTC and CUETO Models to Predict Recurrence and Progression in High-risk Non-muscle-invasive Bladder Cancer Patients - Pazır, Yaşar; Esmeray, Abdullah; Gelmis, Mucahit; Caglar, Ufuk; Ozgor, Faruk; Sarılar, Omer; Akbulut, Fatih (Urology Journal, 2024)
Purpose: To evaluate the performance of the European Organization for Research and Treatment of Cancer (EORTC) and the Spanish Urological Club for Oncological Treatment (CUETO) risk scoring models in non-muscle-invasive bladder cancer (NMIBC) patients defined as high risk according to European Association of Urology guidelines and managed based on current recommendations. Material and Methods: Data from 187 high-risk NMIBC patients treated at a tertiary center between July 2010 and November 2021 were analyzed retrospectively. One- and five-year recurrence- and progression-free survival were assessed for each patient using the EORTC and CUETO risk scores. The patients were divided into four risk groups according to their risk scores as low, medium-low, medium-high and high risk, as indicated in the models. Discriminative ability was evaluated with the Harrell's concordance index (c-index). Results: Both risk scoring models overestimated the risk of recurrence and progression at one and five years. Only the prediction of recurrence at five years in the high risk group according to the CUETO model was compatible with our cohort. CUETO (c-indices for recurrence and progression were 0.802 and 0.834, respectively) exhibited better discrimination than EORTC (0.722 for recurrence and 0.752 for progression) in the prediction of disease recurrence and progression. Conclusion: The CUETO model was superior to the EORTC model in predicting recurrence and progression and stratifying patients with different prognoses in our high-risk NMIBC patient population treated according to current guideline recommendations. However, both models overestimated the probability of disease recurrence and progression. Only the probability of recurrence at five years in the high-risk group of the CUETO model was compatible with our cohort.